The expression and significance of p53 protein and Ki-67 protein in pterygium - Ljubojević Vesna; Gajanin Radoslav; Amidžić Ljiljana; Vujković Zoran (Vojnosanitetski Pregled)
Background/Aim. Pterygium is considered to be a degenerative disease of the conjunctiva, however, the presence of tumor markers in pterygium reinforces the hypothesis that this lesion is similar to tumor. Inactivation of p53 function removes an obstacle to increased proliferation. Factors affecting the prevalence of p53 expression in pterygium deserve investigation. The aim of the study was to investigate the expression of p53 and Ki-67 proteins in pterygium and normal conjunctiva, the effects of gender and age on p53 expression, and the relationship between the expression of p53 and Ki-67 proteins. Methods. A total of 34 samples of pterygium and 34 samples of the normal conjunctiva were analyzed. The samples were studied by immunohistochemistry using antibodies against p53 and Ki-67. Results. Totally 15 (44%) samples of pterygia were p53 positive. Correlations between the expression of p53 protein and sex, and age were not established. The number of Ki-67 positive cells in pterygium (9.74%) was significantly higher than the number of Ki-67 positive cells in the normal conjunctiva (1.74%), (p = 0.001). Between the expression of p53 protein and Ki-67 protein in pterygium there was a significant positive correlation (p = 0.000). Conclusion. The prevalence of p53 positive samples of pterygium was 44%. The influence of sex and age on p53 protein expression in pterygium was not found. The increased proliferative acivity was present in the epithelium of pterygium. The expression of Ki-67 protein is associated with the expression of p53 protein in pterygium. The findings of our study support the thesis of pterygium as tissue growth disorder.